FAKTOR-FAKTOR YANG MEMPENGARUHI CUSTOMER LOYALTY INDUSTRI ASURANSI DI YOGYAKARTA - Petra Surya Wijaya; Kunto Wibisono; Santi Budiman (Fakultas Bisnis UKDW, 2019)
Research on the insurance industry in Indonesia is an interesting study to do. The development of the insurance industry in Indonesia has increased by an average of 30% per year, even in 2016 there was an increase of around 78.1% compared to 2015. This makes competition among insurance companies more stringent. The topic of loyalty in the insurance industry is important for the survival of an insurance company.This study aims to examine the effect of salesperson expertise, subjective norms, service quality, customer satisfaction, commitment, corporate image, switching intention, and communication on customer loyalty. A total of 100 questionnaires were distributed to insurance users in Yogyakarta using purposive sampling. The results of the study state that all hypotheses built can be supported, or that there is a significant influence on salesperson expertise, subjective norms, service quality, customer satisfaction, commitment, corporate image, switching intention, and communication on customer loyalty. Keywords:loyalty, salesperson expertise, subjective norms, service quality, customer satisfaction, commitment, corporate image, switching intention, and communication ABSTRAK Penelitian tentang industri asuransi di Indonesia adalah studi yang menarik untuk dilakukan. Perkembangan industri asuransi di Indonesia telah meningkat rata-rata 30% per tahun, bahkan pada tahun 2016 ada peningkatan sekitar 78,1% dibandingkan tahun 2015. Hal ini membuat persaingan antar perusahaan asuransi semakin ketat. Topik kesetiaan dalam industri asuransi penting untuk kelangsungan hidup perusahaan asuransi. Penelitian ini bertujuan untuk menguji pengaruh keahlian tenaga penjual, norma subyektif, kualitas layanan, kepuasan pelanggan, komitmen, citra perusahaan, niat beralih, dan komunikasi terhadap loyalitas pelanggan. Sebanyak 100 kuesioner dibagikan kepada pengguna asuransi di Yogyakarta menggunakan purposive sampling. Hasil penelitian menyatakan bahwa semua hipotesis yang dibangun dapat didukung, atau bahwa ada pengaruh yang signifikan terhadap keahlian tenaga penjual, norma subjektif, kualitas layanan, kepuasan pelanggan, komitmen, citra perusahaan, niat beralih, dan komunikasi pada loyalitas pelanggan. Kata kunci: kesetiaan, keahlian tenaga penjual, norma subjektif, kualitas layanan, kepuasan pelanggan, komitmen, citra perusahaan, niat beralih, dan komunikasi